A visual programming framework for wireless sensor networks in smart home applications - Serna, M. Angeles; Sreenan, Cormac J.; Fedor, Szymon (2015 IEEE Tenth International Conference on Intelligent Sensors, Sensor Networks and Information Processing (ISSNIP), 2015)
Most of the currently deployed integrated home management products require an experienced technician to install and configure the system. In this paper, we build upon the Internet of Things (IoT) paradigm, with the aim of delivering networked solutions that enable multi-node wireless sensor networks (WSNs) to connect to the Internet in a secure, simple and efficient way. We also describe the design and implementation of a smart-home management system. The system is composed of a lightweight tool with an intuitive user interface for commissioning of IP-enabled WSNs. The solution includes a visual programming interface with a common framework for discovering smart home services on the WSN, and a code analysis and translation engine to generate Python code. This engine analyses the application rules defined with the graphical user interface and translates them into distributed application scripts. The system also includes modules to plan the optimization of the deployment, and deploy and start the generated code. In this paper we present a prototype of the system, with the visual programming solution and code generation module.